2009
DOI: 10.1590/s0103-84782009005000212
|View full text |Cite
|
Sign up to set email alerts
|

Tolerância à germinação na espiga em cultivares de trigo colhido na maturação fisiológica

Abstract: Tolerância à germinação na espiga em cultivares de trigo colhido na maturação fisiológicaSprouting tolerance on spikes in wheat cultivars harvested in the physiological ripening

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
1
6
0
2
Order By: Relevance
“…This differentiation of the genotypes was not observed for the rainfall simulator and germination chamber methods, which grouped the Frontana, IPR Catuara and Quartzo genotypes in the same category of spike sprouting response. [13] stated that rainfall simulation in a controlled environment was efficient in promoting sprouting only in susceptible cultivars; this result was confirmed by the present study, in which both the rainfall simulator and germination chamber methods were able to differentiate genotype BRS 220 (susceptible) from the other evaluated genotypes, showing percentages of grain sprouting per spike of 56.11% and 37.59%, respectively. In contrast, Gavazza et al [6], in an evaluation of the sprouting of wheat genotypes, observed that the rainfall simulation method was best suited for evaluating cultivars in terms of preharvest sprouting regardless of harvest time and evaluation site.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This differentiation of the genotypes was not observed for the rainfall simulator and germination chamber methods, which grouped the Frontana, IPR Catuara and Quartzo genotypes in the same category of spike sprouting response. [13] stated that rainfall simulation in a controlled environment was efficient in promoting sprouting only in susceptible cultivars; this result was confirmed by the present study, in which both the rainfall simulator and germination chamber methods were able to differentiate genotype BRS 220 (susceptible) from the other evaluated genotypes, showing percentages of grain sprouting per spike of 56.11% and 37.59%, respectively. In contrast, Gavazza et al [6], in an evaluation of the sprouting of wheat genotypes, observed that the rainfall simulation method was best suited for evaluating cultivars in terms of preharvest sprouting regardless of harvest time and evaluation site.…”
Section: Resultssupporting
confidence: 88%
“…Franco et al [13] had previously observed differences between genotypes in the number of grains per spike in the Palotina municipality, indicating the superiority of the CD 104, BRS 208 and Frontana cultivars. Similarly, these authors stated that the domestic wheat derived from Frontana likely transmitted the ability to produce a higher number of grains per spike to their offspring, which may have contributed to the increase in the grain yield of new cultivars.…”
Section: Resultsmentioning
confidence: 93%
“…The duration of a test for sprouting resistance in a rain simulator depends on the weather conditions (Bizova et al, 2011;DePauw et al, 2012) and the type of evaluation (Paterson et al, 1989). Test durations between 60 and 120 h have been used for visual evaluations of genotypes (Franco et al, 2009;Gavazza et al, 2012;Shorter et al, 2005;Singh et al, 2014). Converting these durations to DD, based on the temperature data reported in each of these studies, it was observed that these researchers conducted their tests at 54 ADD (Shorter et al 2005), 59 ADD (Gavazza et al, 2012) and 70 ADD (Singh et al, 2014).…”
Section: R E S U Lt S a N D Discussionmentioning
confidence: 99%
“…There are several methods to evaluate PHS and these include artificial sprouting of whole (intact) spikes, germination tests, natural weathering of crop in field trials, artificial weathering trials, and indirect assessment of sprouting by measuring Hagberg FN and molecular markers (DePauw et al ., 2012). Among these, the artificial weathering trials have been used to evaluate a large number of genotypes quickly and to eliminate inferior ones (Bassoi et al ., 2006; Franco et al , 2009; MacMaster and Derera, 1976). The time period in the assessments of PHS in rain simulators varied from 60 h (Franco et al , 2009; Gavazza et al ., 2012) to 96 h (Shorter et al ., 2005) and as much as 120 h (Singh et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Vários fatores podem contribuir para uma maior tolerância à germinação na espiga, como a redução dos níveis de alfa-amilase nos grãos, a presença de inibidores de germinação, redução da absorção de água pelos grãos e respostas alteradas para hormônios (FLINTHAM, 2000;ZANETTI et al, 2000;HIMI et al, 2002;MARES et al, 2005). Adicionalmente, a falta de dormência adequada das sementes é a principal razão para a PHS, sendo destacada como uma característica governada por múltiplos genes (LI et al, 2004 (BASSOI et al, 2006;FRANCO et al, 2009;OKUYAMA et al, 2017 Embora a variabilidade genética existente no triticale para a resistência à PHS e para o NQ seja menor que a disponível no trigo, ela parece ser suficiente para que, através do melhoramento genético, novas cultivares superiores possam ser geradas (NEDEL et al 1983b;HAESAERT;DE BAETS, 1996;OETTLER, 2005;ALARU et al 2008;BIZOVA et al 2011).…”
Section: Characterization Of Triticale Genotypes For Germination Toleunclassified